Sacralization of Epidural Block with Repeated Doses of 0.25% Bupivacaine during Labor. Issue 6 (November 1990) - Yarnell, Ralph W.; Tierney, Eamon; Ewing, David A.; Smith, Heather M.
Abstract : A descriptive analysis of the progression of epidural block with repeated doses of 0.25% bupivacaine was performed, assessing pain relief (visual analog scoring), dermatomal spread of sensory and motor block, and the associated management and outcome of labor. The influence of epinephrine 1:200, 000 on these observations was also assessed by the random assignment of study patients into two groups, one receiving 10 ml of 0.25% bupivacaine plain (n = 28) and another group receiving 10 ml of 0.25% bupivacaine with commercially added epinephrine 1:200, 000 (n = 27). Only primigravid patients were studied. Data comparisons were considered significant at p < 0.05. With repeated doses of 0.25% bupivacaine, administered within fixed dosing intervals of 60-90 minutes, there was an increasing spread of sensory block toward sacral dermatomes while the upper level of sensory block did not change. Sacral sensory analgesia was present in only 3.5% of patients after the first dose of bupivacaine but was evident in 63.2% of patients following the fourth epidural injection. A similar increase in the number of patients with significant motor weakness was also seen as the number of top-up doses increased. A comparison of patients receiving plain solutions and epinephrine containing bupivacaine showed similar demographic profiles between the groups. Both groups received a similar dose of bupivacaine and experienced comparable management and outcome of labor. Epinephrine in a 1:200, 000 concentration did not influence the changing characteristics of the epidural block over time. The duration of labor was not significantly different between groups (10.3 ± 5.2 hours for the plain group and 11.0 ± 4.7 hours for the epinephrine group). It is important to appreciate the changing pattern of segmental epidural block with repeated dosings of 0.25% bupivacaine to best anticipate adjustments to the technique that may be required as labor progresses. Similar studies are needed to assess changing patterns of neural block over time when continuous epidural infusion techniques are used.